Genetics of Cardiovascular Disease: How Far Are We from Personalized CVD Risk Prediction and Management? - Vrablik, Michal; Dlouha, Dana; Todorovova, Veronika; Stefler, Denes; Hubacek, Jaroslav A (International journal of molecular sciences, 2021)
Despite the rapid progress in diagnosis and treatment of cardiovascular disease (CVD), this disease remains a major cause of mortality and morbidity. Recent progress over the last two decades in the field of molecular genetics, especially with new tools such as genome-wide association studies, has helped to identify new genes and their variants, which can be used for calculations of risk, prediction of treatment efficacy, or detection of subjects prone to drug side effects. Although the use of genetic risk scores further improves CVD prediction, the significance is not unambiguous, and some subjects at risk remain undetected. Further research directions should focus on the "second level" of genetic information, namely, regulatory molecules (miRNAs) and epigenetic changes, predominantly DNA methylation and gene-environment interactions.
Keywords: Genetic Testing; gene; gene score; Genetic Predisposition to Disease; epigenetic; genetické testování; individualizovaná medicína; Genome-Wide Association Study; interaction; kardiovaskulární nemoci; Nutrigenomics; Animals; lidé; Humans; cardiovascular disease; zvířata; nutrigenomika; Cardiovascular Diseases; Precision Medicine; genetická predispozice k nemoci; celogenomová asociační studie; polymorphism